PENGARUH MENARI TARI BALIH-BALIHAN TERHADAP HARGA DIRI REMAJA TUNARUNGU DI SLB B BALI - Swandi, Ni Luh Indah Desira; Valentina, Tience Debora (Jurnal Psikologi Udayana, 2014)
Deaf adolescent has different characteristics in speech and language (Effendi, 2009). These differences cause difficulties in interacting and dealing with adolescent developmental tasks so that adolescent feels isolated and has low self-esteem (Halimah & Elcamila, 2010). One way to improve self-esteem is by dancing, as a form of self-expression and development of confidence in the self competence (Branden, 2005).  This study aimed to determine the effect of dancing Balih-balihan toward self esteem of deaf adolescent in Bali. The sampling technique used in this study is two stages cluster sampling. Subjects of this research are 40 deaf students of SLB B in Bali, from age 11-24 years old. The research method that used is ex post facto. Data is collected by using scale of self-esteem based on aspects by Coopersmith. The dance variable is divided into two groups named the control and the experimental group, in this case the experimental group has been doing dance activity as a compulsory activity in schools. Data were analyzed by using Independent Sample T-Test. The validity test shows there are 20 valid items with a reliability coefficient of 0.384. The result of data analysis shows data distribution is normal and homogeneous. Independent Sample T-Test results t values 1.542 with a probability value 0.131 (p> 0.05). It means there is no significant effect of dancing Balih-balihan toward self-esteem of deaf adolescent in Bali. Keywords: Dancing Balih-balihan, self-esteem, deaf adolescent